Microstructural, morphological and dielectric properties of Mo, Se co-doped Ba0.6Sr0.4TiO3 perovskites - Kelele, Kiflom Gebremedhn; Ananda Murthy, H. C.; Balachandran, Ruthramurthy; Tadesse, Aschalew; Tan, K. B. (KeAi Publishing Communications, 2023)
Previous studies have shown that co-doping of BST resulted in enhanced dielectric properties of BST. Meanwhile, no work was reported about effect of Mo, Se on the dielectric properties of Barium strontium titanate (BST). Hence, this report was expected to contribute on the ways of enhancing the dielectric activity of BST through doping. The purpose of the research was to investigate the microstructural, morphological as well as the dielectric properties of BST and Mo, Se co-doped BST following their slow injection sol–gel synthesis and calcined at 800 °C. The effective synthesis of cubic Ba0.6(Sr0.4-xSex)(MoyTi1-y)O3 nanopowder has been confirmed using FT-IR, Raman spectroscopy, EDS, and XRD techniques where the presence of every element and the empirical formula matched with the predicted ones. The average crystallite size of BST increased from 23.97 nm to 26.18 nm after doping. Likewise, the average grain size elevated from 40.13 nm to 53.27 nm accompanied by the elevation of the number of agglomerated crystallites in a grain per SEM particle (1.98 to 3.55). The average particle size of Mo and Se co-doped BST was found as 26.63 nm. The lowering of pore size as well as pore volume of BST was also observed after doping. All these properties led to the elevation of dielectric constant (from 248.8 to 953.00) and lowering of the dielectric loss (from 0.1620 to 0.0928). Therefore, the Mo, Se co-doped BST possessed such varied properties from BST which makes it to be effectively utilized in capacitive applications such as supercapacitors.